Agritourism as the Epitome of India’s Sustainability Culture : A Narrative Review - Dsouza, Komal Jenifer; Shetty, Ankitha; K., Rajasekharan Pillai (Indian Journal of Marketing, 2024)
Purpose : Agritourism is thought to be one of the tourism industry’s most sustainable byproducts in the age of sustainable practices. India is adjusting to the notion that agritourism, a prospective and expanding sector of the tourism industry, could place the nation on the global agritourism map and transform the nature of the travel and tourist industry. Methodology : This paper reviewed the trajectory of agritourism in India by adopting a narrative synthesis approach to consolidate the textual descriptions available in the public domain by using SANRA â€“ Scale for the Assessment of Narrative Review Articles (2019). The search yielded n = 552 results. N = 45 fulfilled the inclusion criteria, i.e., n = 18 tourism policies of Indian states and UTs, n = 15 gray literature, and n = 12 scientific articles. Findings : Agritourism has a lot of potential, but it also confronts challenges like strained stakeholder relationships and a lack of awareness among businesses about sustainability. There is still no national enabling policy in place, despite intermittent efforts from a few states. Practical Implications : Futuristically, a definitive roadmap could contribute toward the sustainable development of Indiaâ€™s agritourism sector. The sector also called for a contemporary yet effective framework through a National Tourism Policy that could encourage more farmers to indulge in sustainable agritourism while also promising outstanding hospitality to those seeking gratifying experience, peace, and tranquillity. Originality : Our study pioneered in offering a definitive roadmap underscored by practical designs, pragmatic strategies, and consistent monitoring that could accelerate India’s agritourism sector and revolutionize the rural prosperity of the country.